Efektivitas Pemanfaatan Canva sebagai Media Pembelajaran Luring - Deliana, Anju; Romalinca, Romalinca; Omerlin, Omerlin; Krisbet, Krisbet; Meldawati, Meldawati (Medan Resource Center, 2023)
This study investigates the effectiveness of learning utilizing Canva-based media. Employing a developmental approach, it includes initial analysis, material identification, preparation, and testing via a questionnaire. Data analysis shows students highly favor Canva learning media, with an average score of 73.8%. The study underscores the pivotal role of audio-visual learning tools, particularly amid the Covid-19 pandemic, in facilitating effective learning. Trial results affirm the media's suitability for educational settings, with questionnaires highlighting its attractive design and clear presentation of material content. This underscores the importance of innovative media in enhancing learning outcomes, especially in challenging circumstances. Furthermore, the study suggests that integrating Canva into the curriculum could significantly contribute to students' engagement and comprehension. These findings emphasize the necessity of adaptable and engaging teaching methods to meet the evolving demands of modern education, particularly in times of crisis.